Biodegradation of waste and pure canola oil by cold-adapted Rhodococcus sp. AQ5-07 from Antarctica - Ibrahim, Salihu (2020)
With the increase in human activities in Antarctic region, the possibility of vegetable oil spillage becomes unavoidably high. The removal of oils including canola oil from the environment and wastewater using biological approaches is needed since the thermal process of oil degradation is ineffective and requires the use of high temperatures. More so, thermal degradation leads to the generation free radicals. Thus, in this present study, the potential canola oil-degrading ability of cold-adapted Rhodococcus sp. AQ5-07 from Antarctica was evaluated using one-factor-at-a-time (OFAT), and response surface method (RSM). The bacterial growth kinetics was examined and screened for biosurfactant production. The ability of Rhodococcus sp. AQ5-07 to degrade canola oil in the presence of different heavy metals and xenobiotics was also tested. Furthermore, canola oil degradation pathway was investigated via whole genome analysis. Rhodococcus sp. strain AQ5-07 was found to have a high canola oil-degrading ability over other strains tested. Considerable degradation (78.60% and 70.14%) of 3% waste and pure canola oil was achieved by this bacterium when incubated with 1.0 g/L ammonium sulphate, 0.3 g/L yeast extract, pH 7.5 and 10% inoculum at 10°C over 72 h incubation period. Optimisation of the medium conditions using response surface methodology (RSM) resulted in an increase in both oil degradations (87.61% and 86.34%). Three out of the 10 heavy metals tested namely mercury (Hg), cadmium (Cd) and silver (Ag) had a significant effect on canola oil degradation at 1 ppm. The IC50 values of the waste canola oil (WCO) for Hg, Cd and Ag were found to be 0.3866, 0.4539 and 0.3217 ppm, respectively. Meanwhile, for the pure canola oil (PCO), the IC50 was found to be Hg (0.2495), Cd (0.5452) and Ag (0.3088), respectively. This shows that the strain can also withstand 10 mg/L acrylamide, 50 mg/L phenol and 0.5% (v/v) diesel, respectively, for both oils. The bacterium was also found to produce high biosurfactant with beta haemolysis, high cellular hydrophobicity of 89.5% and 83.5% in hexadecane and tetradecane, respectively. The strain displayed 55 mm drop collapse with an oil displacement of 48 mm. Emulsification test (E24) revealed the highest emulsification index of 92% in hexadecane. Haldane and Yano model best describes the kinetics of the strain growth, the calculated constants for Haldane model such as maximum growth rate (μmax), half saturation constant for maximal growth (Ks), and growth inhibition constant (Ki) tolerated were 0.142 h-1, 7.743% (v/v) and 0.399% (v/v), respectively, whereas those for Yano model were 0.096 h-1, 3.0% (v/v) and 4.527% (v/v), respectively. Lastly, the bacterium genome was sequenced using whole genome sequencing (WGS). The WGS was assembled into a draft genome of 6,753,902 bp with G+C content of 62.4% and 828.79x sequencing depth of coverage. It comprises 4 contigs with sizes of 81,655, 134,292, 214,483 and 6,323,472 bp. The smaller contigs could represent plasmids. The coding sequences (CDSs) contained a total of 6,350 annotated genes, 53 tRNA and 15 rRNA. The WGS showed that Rhodococcus sp. AQ5-07 was closely related to Rhodococcus erythropolis NBRC 15547 and Rhodococcus qingshengii JCM 15477, respectively. Analyses revealed the presence of lipase genes responsible for lipid degradation. This study therefore confirmed the possible use of cold-adapted Rhodococcus sp. AQ5-07 in biodegradation of canola oil-polluted Antarctic soils at low temperature, as it is disease free, eco-friendly, easier and cheaper.